Wakaf dan Pengembangan Pendidikan Islam di Indonesia - Mutmainah, Mutmainah (JOIES (Journal of Islamic Education Studies), 2016)
The term wakaf has been known since the time of the Prophet, on the second year of the Hegira. Ithas a very close relationshipbetween Islamic education and wakaf. Wakaf institutions become the financial resources for the activities of Islamic education. Until nowadays, especially in Indonesia, wakaf remains to be one of the pillars of funding for education. Initially, it is in the form of the landswakaf. Furthermore, in 2002 the Indonesian Ulama Council issued a fatwa allowing money wakaf (cashwakaf / waqf al nuqud) on condition that the principal value of wakaf must be guaranteed for its sustainability. In modern times, moneywakafisinterpreted by donating their valuables such as securities to a financial guarantee institution. Furthermore, the results of these guarantees are endowed to help the education.